How temperature variation affects white-rot fungi mycelial growth dynamics: A nonlinear mixed models approach - Negrão, Djanira Rodrigues [UNESP]; Mischan, Martha Maria [UNESP]; de Pinho, Sheila Zambello [UNESP]; de Carvalho, Lídia Raquel [UNESP]; Gomes, Rafaela Lanças [UNESP]; de Souza Passos, José Raimundo [UNESP] (Elsevier, 2021)
This study aimed to model mycelial growth in a factorial experiment with two species of white rot fungi growing at five temperatures. The nonlinear models evaluated were logistic, Gompertz, Weibull and von Bertalanffy. The adjustments were performed first by evaluating the fixed and mixed-effects models with random effects, added to the fixed parameters. Then, the best adjusted model was improved by an adequated covariance structure, and dummy variables were added to the parameters asymptote (α) and abscissa of the inflection point (β) in the model in order to verify the effect of the experiment factors, species and temperatures on the regression parameters. The criteria used to compare models were residual variance and Akaike information criterion. Gompertz and von Bertalanffy mixed-effects models were better adjusted. The parameters differed between species. Moreover, the linear and quadratic effects of temperature evaluated in each species were significant. The models were reparametrized in order to consider two parameters of interest: velocity (μ) at the inflection point and lag time (λ). The maximum growth velocity was obtained at 25.4 °C by S. ostrea, while T. villosa was achieved at 30.5 °C; both fungi suffered less lag time by increasing the temperature.
Keywords: Dummy variables; Gompertz; Logistic; von Bertalanffy; Weibull